Mutual Integration in Immigration Society An Epistemic Argument - Wang, Bodi (Campus Verlag, 2023)
The public culture of the receiving society and the dominant understanding of belonging and political membership can influence the social participation of immigrants as much as immigration law. However, current discussions of integration focus primarily on the distribution of rights and neglect the role of tacit knowledge. Through a systematical and philosophical analysis of identity's role in policy-making, governance and social practice, Bodi Wang shows how a one-sided understanding of integration resembles »assimilation« and why integration should be expected from locals as well. Weaving together extensive findings in sociology, history, critical race theory and Chinese philosophy with ethics and migration studies, this book provides a compelling argument for adopting the concept of »mutual integration« to overcome injustice and to enhance social solidarity.